Hepatitis E Vaccine to Prevent Morbidity and Mortality During Epidemics. (4th November 2014) - Nelson, Kenrad E.; Shih, James W. K.; Zhang, Jun; Zhao, Qinjian; Xia, Ningshao; Ticehurst, John R.; Labrique, Alain B.
Abstract: Recurrent, large, waterborne epidemics of hepatitis E virus (HEV) occur regularly after monsoon rains contaminate water supplies in Asia or during humanitarian crises in Africa. These epidemics commonly affect thousands of persons, and it has a high mortality in pregnant women who become infected. Although a subunit HEV vaccine has been developed by Chinese investigators and was found to be highly effective and safe in a large clinical trial, this vaccine is only available in China. Until it is prequalified by the World Health Organization, the vaccine may not be available for use outside of China in low-income countries that lack national vaccine regulatory agencies. In this manuscript, we explore possible strategies for providing access to this potentially important vaccine for international use in responding to epidemics of HEV in low-resource countries.